2006
DOI: 10.1007/s11099-006-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Ambient levels of UV-B in Hawaii combined with nutrient deficiency decrease photosynthesis in near-isogenic maize lines varying in leaf flavonoids: Flavonoids decrease photoinhibition in plants exposed to UV-B

Abstract: Near-isogenic lines of maize varying in their genes for flavonoid biosynthesis were utilized to examine the effects of foliar flavonoids and nutrient deficiency on maximum net photosynthetic rate (P N ) and chlorophyll (Chl) fluorescence (F v /F m ) in response to ultraviolet-B (UV-B) radiation. Plants with deficient (30 to 70 % lower N, K, Mn, Fe, and Zn) and sufficient nutrients were exposed to four irradiation regimes: (1) no UV-B with solar photosynthetically active radiation (PAR), (2) two day shift to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Anthocyanin mitigates the damaging effects on PSA by screening UV-B penetration, while flavonoids, besides their anti-oxidant property, diminish the damaging effect by attenuating UV-B radiation (Holton and Cornish 1995, Mohr and Schopfer 1995, Lau et al 2006. The protection of DNA by anthocyanin and flavonoids was detected by Stapleton and Walbot (1994).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin mitigates the damaging effects on PSA by screening UV-B penetration, while flavonoids, besides their anti-oxidant property, diminish the damaging effect by attenuating UV-B radiation (Holton and Cornish 1995, Mohr and Schopfer 1995, Lau et al 2006. The protection of DNA by anthocyanin and flavonoids was detected by Stapleton and Walbot (1994).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient supply has also been shown to did not affect well--fertilized plants [40]. UV--B (7.2 kJ m −2 day −1 UV above ambient)…”
mentioning
confidence: 99%
“…It has been reported that the negative effect of the nutrient scarcity on the development of many crops is associated with the reduction of Pn, F V /F M , and g s , in corn [20] while in sugar beet, the low Pi reduced CO 2 assimilation by 33% [21]. This negative effect of low Pi supply can be related to many aspects such as reduction of chlorophyll a and b, affecting also, the PSI and PSII efficiency [20].…”
Section: Discussionmentioning
confidence: 99%
“…This negative effect of low Pi supply can be related to many aspects such as reduction of chlorophyll a and b, affecting also, the PSI and PSII efficiency [20]. Furthermore, Pi is necessary to couple photosynthetic reactions in the dark and light phases, because of its structural and regulatory role in energy conservation and CO 2 assimilation [22].…”
Section: Discussionmentioning
confidence: 99%